Expropriation and the location of farmland investment: A theoretical investigation into the land rush - Alfredo R. Rosete (University of Massachusetts, Department of Economics, 2015)
The sudden rise in land acquisitions in developing countries during the last decade has drawn the attention of scholars and think tanks. A set of recent papers by Deininger (2011), Deininger (2013), and Arezki et al. (2013) sought to understand the empirical determinants of the land rush. They find that investors tend to target countries that have little regard for local land rights. This is a puzzle, given the economic literature on investment location. By locating in such countries, investors may be foregoing other advantages that generate more revenue. What does such a result say about both the nature of the investment projects, and the productive characteristics of the target countries? In this paper, I attempt to answer this question using a game-theoretic model where investors can use expropriation as a credible threat vis a vis smallholders, consistent with case studies and empirical data from actual land deals. I show that the credible threat of expropriation lowers the investor's cost of locating to a country by reducing the necessary remuneration to smallholders for access to land, resulting in adverse incorporation. Further, I show that investors will locate in countries with weak land governance whenever they anticipate similar levels of revenue among the set of countries they target, or, whenever they can guarantee a similar level of investor protections.
Keywords: F21; O13; Q15; Q34; C79; 330; Land Acquisitions; Agribusiness; Governance; Contest Games; Investment Location